Developmental Trajectories of Aggressive and Non-Aggressive Conduct Problems - Maughan, Barbara (Journal of quantitative criminology, 2000)
Modeling the heterogeneous trajectories along which antisocial behaviordevelops in childhood and adolescence may contribute in important waysto understanding antecedents of offending in adult life. This paperexamines the development of aggressive and non-aggressive conduct problemsin the Great Smoky Mountains Study of Youth, a longitudinal study in thesoutheastern United States. Aggressive and non-aggressive conduct problemsof clinical severity, police contact and arrest, and family andenvironmental correlates were assessed in four annual interviews for789 boys and 630 girls aged 9–13 at first interview. The bestfitting latent class model identified three developmental trajectories:stable low problem levels, stable high problem levels, and declining levelsof conduct problems, for both aggressive and non-aggressive behaviors. Boyswere over-represented in the stable high trajectory class on the aggressivetrajectory, but sex differences in non-aggressive trajectories were lessmarked. The overlap between aggressive and non-aggressive trajectory classeswas quite limited. Both classifications showed strong associations withrisks of police contact and arrest in early adolescence, and with measuresof family adversity. The results are discussed in relation to developmentalmodels of conduct disorder and delinquency.